(untitled) (Swiss Medical Weekly, 2025)
Can lifesaving be punishable? Performing resuscitation in an emergency places individuals under great pressure. Empirical studies indicate that potential helpers often hesitate to intervene for fear of legal consequences. However, this concern is unfounded. The article examines four scenarios: death despite resuscitation, harmful or unwanted resuscitation, and omission of aid. The conclusion is unequivocal: in case of doubt, initiating resuscitation (“in dubio pro REA”) is legally safe. Only in cases where it is clearly established that resuscitation is not desired does the exception apply, meaning that no assistance should be rendered (“no means no”). This article analyses criminal liability risks in resuscitation based on Swiss law. Nevertheless, the findings are broadly transferable to other jurisdictions, as the relevant offences are universally codified.